The effect of forward-bent posture of upper body in acceleration phase on 100m sprint performance - Adachi, T.; Yasue, M.; Fukuda, T.; Ueda, T. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The technique called forward-bent posture is used in the acceleration phase of the 100m sprint running. The performance was influenced beccause of maintaining forward-bent posture of different distances (Ito, 2010). In this study, there were two purposes. First, to determine whether subjects can carry out accelerating with longer and shorter distance. Second, to reveal the influence of the running velocity (RV), the stride length (SL) and the stride frequency (SF) from the point of view of motion and electromyogram (EMG) of the lower extremities. Methods: Nine collegiate sprinters run 100m sprint by using three patterns of acceleration patterns. First acceleration pattern was the usual method of raising forward-bent posture which was used in the daily training. Second and third acceleration pattern was the longer and shorter method than the usual method of raising forward-bent posture, respectively. The forward angle of every 10m in 0-40m interval were calculated. Subsequently, six collegiate sprinters run 100m sprint by using three types of acceleration patterns. RV, SL and SF were calculated. In addition, the hip, knee and angle joints angle of 0-40m interval and EMG of gluteus maximus, rectus femoris, biceps femoris and gastrocnemius of 0-100m interval were measured. Results: It was thought that subjects could carry out accelerating by longer and shorter. In the RV of 0-100m, the value of the longer raising method was significantly higher than that of the shorter raising one. In the SL of 0-30m, 0-40m, 0-50m, 0-60m, 0-70m and 0-90m, the value of the longer raising method was significantly higher than that of the shorter one. Discussion: It was estimated that what the knee and ankle angle increased was caused to the reduction of the force to kick the ground because of the kick the ground with a higher center of gravity in the contact phase (Iwai, 1997). In the angle of the knee and ankle joints at the 15m and the 35m points in this phase, the value of the shorter raising method was significantly higher than the other two methods. This was likely to be shorter the stride during running. It was reported that there were the changes, and no changes in relation to muscle activity with the different joint angle of the lower limb (Ema, 2010). By comparing this, the differences in running velocity could not be explained from the amount of muscle discharge of lower limb. However, in this study, the ratio of each muscle activity might be changed among three different methods during accelerating.